A PHILOSOPHY OF LANGUAGE ON THE INDONESIAN SUBJECTIVE THIRD-PERSON SINGULAR PRONOUNS WITHIN THEIR PROBABLE ENGLISH EQUIVALENTS - Jumanto Jumanto (Fakultas Ilmu Budaya, Universitas Dian Nuswantoro, 2015)
This simple research article is about a philosophy of language on the Indonesian subjective third-person singular pronouns DIA and IA and their probable equivalents in the English language. The philosophy involves discussions on the nature of meaning of DIA and IA, the use of DIA and IA, the cognition of DIA and IA, and the relationship between DIA and IA and reality in Indonesian context. English probable equivalents are analyzed and elaborated to contribute a conclusion on new forms and functions of the subjective pronouns DIA and IA in Indonesian context. This article is more of philosophy rather than of discourse analysis, as it draws our attention to the fact that language use is, indeed, a matter of probability which later may evolve into being or a reality, i.e. the forms and functions of DIA and IA in formal use as well as practical use in Indonesian context.Keywords: Subjective Pronouns, Third-Person Singular Pronouns, Indonesian Subjective Third-Person Singular Pronouns, English Subjective Third-Person Singular Pronouns, Word Equivalents